eCM 2016
DOI: 10.22203/ecm.v031a20
|View full text |Cite
|
Sign up to set email alerts
|

A surprisingly poor correlation between in vitro and in vivo testing of biomaterials for bone regeneration: results of a multicentre analysis

Abstract: New regenerative materials and approaches need to be assessed through reliable and comparable methods for rapid translation to the clinic. There is a considerable need for proven in vitro assays that are able to reduce the burden on animal testing, by allowing assessment of biomaterial utility predictive of the results currently obtained through in vivo studies. The purpose of this multicentre review was to investigate the correlation between existing in vitro results with in vivo outcomes observed for a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 52 publications
0
108
0
1
Order By: Relevance
“…Complementary, screening for biomaterials can be supported by in vitro tests. However, in vitro tests often entail a poor correlation between in vitro and in vivo 19 . By comparing test conditions in a human in vitro biomaterial study, we identified an experimental setup that closely correlates to the fibrotic response observed in animal and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary, screening for biomaterials can be supported by in vitro tests. However, in vitro tests often entail a poor correlation between in vitro and in vivo 19 . By comparing test conditions in a human in vitro biomaterial study, we identified an experimental setup that closely correlates to the fibrotic response observed in animal and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…By complementation of existing in vivo models, such an approach follows the Russell and Burch’s 3R aspect of reducing animal burden 20, 78 . However, a poor correlation between in vitro and in vivo assessments confirms a clear need for predictive in vitro biomaterial tests 19 . The inadequacy of the current in vitro assessment strengthens our comparative approach to identify predictive test conditions for the development of a novel biomaterial in vitro test platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to scaffold microstructure, high‐resolution XCT enables the assessment of newly formed bone and biomaterial degradation in animal models (Gauthier et al ., ; Jones et al ., ; van Lenthe & Müller, ; Boerckel et al ., ; Kerckhofs et al ., ; Sweedy et al ., ). Certainly, bone defect animal models remain essential for preclinical research of novel biomaterials (Hulsart‐Billström et al ., ), overcoming limitations of in vitro studies due to the reduced complexity of the environment. The microstructure, biological properties and mechanical competence of the implanted biomaterials can be then evaluated to demonstrate their ability produce bone that is comparable to the native tissue they are meant to replace, supporting load‐bearing regions.…”
Section: Bone Regeneration Xct Analysismentioning
confidence: 99%
“…Bone defect animal models remain essential tools for preclinical research of novel biomaterials (Pearce et al, 2007;Muschler et al, 2010;Li et al, 2015;El-Rashidy et al, 2017), overcoming limitations of in vitro studies due to the reduced complexity of the environment. Several animal models have been used to study biomaterial-mediated bone regeneration in critical-sized defects: segmental-defects and critical-sized cranial defects models in rats and mice are widely employed for the evaluation of biomaterial capability for bone regeneration (Hulsart-Billström et al, 2016). However, segmental-defect models generally require the use of internal or external fixators, thus bone regeneration is not only affected by the biomaterial action but the stiffness of such fixation device (Einhorn et al, 1984;Yang et al, 2003;Kanczler et al, 2008;Kanczler et al, 2010;Kaipel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%